Tumor lysis with LTX-401 creates anticancer immunity. (3rd July 2019) - Xie, Wei; Mondragón, Laura; Mauseth, Brynjar; Wang, Yan; Pol, Jonathan; Lévesque, Sarah; Zhou, Heng; Yamazaki, Takahiro; Eksteen, Johannes J.; Zitvogel, Laurence; Sveinbjørnsson, Baldur; Rekdal, Øystein; et al.
ABSTRACT: Local immunotherapies such as the intratumoral injection of oncolytic compounds aim at reinstating and enhancing systemic anticancer immune responses. LTX-315 is a first-in-class, clinically evaluated oncolytic peptide-based local immunotherapy that meets these criteria. Here, we show that LTX-401, yet another oncolytic compound designed for local immunotherapy, depicts a similar safety profile and that sequential local inoculation of LTX-401 was able to cure immunocompetent host from subcutaneous MCA205 and TC-1 cancers. Cured animals exhibited long-term immune memory effects that rendered them resistant to rechallenge with syngeneic tumors. Nevertheless, the local treatment with LTX-401 alone had only limited abscopal effects on secondary contralateral lesions. Anticancer effects resulting from single as well as sequential injections of LTX-401 were boosted in combination with PD-1 and CTLA-4 immune checkpoint blockade (ICB), and sequential LTX-401 treatment combined with double ICB exhibited strong abscopal antineoplastic effects on contralateral tumors underlining the potency of this combination therapy.